(NsPRAWO^NIK PO TEORII PODWODNOGO WIDENIQ (B/s - (NdOLIN(B, (NlEW sERGEEWI^s; (NlEWIN(B, (NiOSIF mARKOWI^s ((Nl(B. :s (NgIDROMETEOIZDAT(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 217-224 (169 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 225-226s
Keywords: (NpRIBORY PODWODNOGO WIDENIQ (B- (NsPRAWO^NIKIs